STUDY Of THE App ROACHES ON THE CIVIC CENTER MASSACRE IN MAGAZINES CARTA CAPITAL AND REVISTA FORUM - Luvizotto, Caroline Kraus [UNESP]; Consalter Amor, Ana Cristina [UNESP]; Caldeira, Priscila Santana [UNESP] (Sbpjor, 2018)
This article analyzes, through content analysis, the coverage made by Carta Capital and Revista FOrum magazines about the Civic Center Massacre, held on April 29, 2015 in Curitiba/PR. Specifically, this study aimed to check how these vehicles represented the episode in question, which reached great repercussion throughout Brazil due to the truculent repression applied by the Military Police of Parana state. We chose the online version of the weekly magazines Carta Capital and Revista Forum since they present themselves as plurals and propose a positive analysis of social movements and collective actions. Both magazines assumed positive editorial positions regarding teachers' manifestations and their motivations, as well as, in a negative way, the police truculence on the fateful day of April 2015.
Keywords: Alternative media; Social movements; Carta Capital; Revista Forum; Civic Center Massacre